CE‐MS‐based serum fingerprinting to track evolution of type 2 diabetes mellitus. Issue 18 (26th June 2015) - Ciborowski, Michal; Adamska, Edyta; Rusak, Magdalena; Godzien, Joanna; Wilk, Juliusz; Citko, Anna; Bauer, Witold; Gorska, Maria; Kretowski, Adam; Barbas, Coral
<x xml:space="preserve">Abstract</x> Development of type 2 diabetes mellitus (T2DM) is preceded by insulin resistance (IR), which may evolve to impaired fasting glucose (IFG) and/or impaired glucose tolerance (IGT). IFG and IGT are considered as prediabetic states (PD). Prediabetes indicates the high risk for the future development of diabetes, it is estimated that up to 70% of prediabetics eventually develop T2DM. The risk of T2DM development is increased in overweight (OW) and obese (OB) people; however normal weight (NW) individuals also suffer from T2DM. The present study was designed to evaluate whether changes in polar metabolites induced by T2DM evolution are different between NW, overweight and obese individuals. CE‐MS serum fingerprinting was performed on 197 serum samples obtained from OW, OB, and NW humans whom were IR, prediabetics, diabetics or with normal glucose homeostasis. Metabolic changes evoked by the progression of T2DM differ between obese, overweight, and normal weight subjects. Based on obtained results several metabolites can be proposed as a promising target to track T2DM evolution; BCAA in OW and NW humans, lysine in OB, while acetylcarnitine and methionine independently on body mass index. Validation of obtained results on larger population is required.